CHANGING APPROACHES TO INDIGENOUS KNOWLEDGE AND ITS RELATIONSHIP WITH SCIENTIFIC KNOWLEDGE - Ngo Thi Puong Lan (Humaniora, 2015)
Prevailing views on indigenous knowledge (IK) rely on a binary contrast between indigenous knowledge and scientific knowledge (SK), where the former is either dismissed as backward or judged superior in terms of its sustainability. I assert instead that we must examine the specific conditions under which people invoke indigenous and/or scientific forms of knowledge. Based on an ethnographic study of the IK of two Mon-Khmer speaking ethnic minority populations, the Xtiêng and the Mạ, in Binh Phuoc province of Vietnam, conducted in 2012 and 2013, this paper re-examines the definition of IK, exploring the relationship between IK and scientific knowledge (SK), and analyzing the changing nature of IK in the present context. In so doing, I suggest that IK is not a static body of knowledge but depends substantively on socio-economic conditions. In local people’s daily lives, they both use IK and SK as resources for navigating their changing life-worlds.